Determinants of Convergence and Disparities in Europe: Innovation, Entrepreneurship and the Processes of Clustering - Andreas P. Cornett; Nils Karl Soerensen (European Regional Science Association (ERSA), 2012)
Innovation and entrepreneurship are key factors in current regional development initiatives, derived from the concepts of new economic growth theory. The aim of this paper is to combine an assessment of innovative and entrepreneurial performance with the spatial distribution and functional linkages of certain types of economic clusters. The hypothesis is that clustered regions with high entrepreneurial and innovative performance have higher growth than non- innovative/entrepreneurial regions or regions with a more scattered economic structure. The clustering and in some cases even the polarization of economic activities metropolitan regions can lead to excess growth, and contribute to a process of convergence between nations, but will also turn regional economic divergence back on the national economic development agenda. The purpose of this paper is to provide in deep information on these processes in an international and perspective based on European empirical evidence. The first part of the paper addresses the development and growth issue in a theoretical development policy perspective. The impacts of innovation (measured by innovation scoreboard data) and entrepreneurship (GEM data etc.) on regional growth are estimated individual and combined as well as dummies for various levels of industrial clustering (measured by location quotients and the change of LQ) are included. Within these groups we study the process of convergence by use of the traditional measures of convergence. The findings are compared with traditional geographical convergence results, enabling an analysis based both on traditional geographical adjacent regions, often characterized by a common institutional framework, and regions characterized by common features in economic performance terms. Based on the empirical results and the findings of the literature survey in the first part of the paper the final section provides an assessment of the overall trends in economic convergence and disparities and the drivers behind this process.
Keywords: 330